230
because 5x23 is 115 x 2 which is 230
If my math is correct this should be a simple equation. First you’d start off by figuring out how much money chicken costs per one pound.
53.28 / 4.5 = $11.84 per pound
Now take how much money the chicken costs per pound and divide it by how much Benjamin spent.
59.20 / 11.84 = 5 pounds
Your answer should be exactly 5 pounds
I apologize if this is incorrect math, but the equation seems simple at first glance.
6)
34, 43, 52, 61, ...
43-34 = 9; 52-43 = 9; 61-52 = 9
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 34
difference: d = 9
so the formula:
![a_n=a+d(n-1)\\\\a_n=34+9(n-1)\\\\a_n = 34+9n-9\\\\\underline{a_n=9n+25}](https://tex.z-dn.net/?f=a_n%3Da%2Bd%28n-1%29%5C%5C%5C%5Ca_n%3D34%2B9%28n-1%29%5C%5C%5C%5Ca_n%20%3D%2034%2B9n-9%5C%5C%5C%5C%5Cunderline%7Ba_n%3D9n%2B25%7D)
7)
10, 6, 2, -2, ...
6-10 = -4; 2-6 = -4; -2-2 = -4
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 10
difference: d = -4
so the formula:
![a_n=a+d(n-1)\\\\a_n=10+(-4)(n-1)\\\\a_n = 10-4n+4\\\\\underline{a_n=-4n+14}](https://tex.z-dn.net/?f=a_n%3Da%2Bd%28n-1%29%5C%5C%5C%5Ca_n%3D10%2B%28-4%29%28n-1%29%5C%5C%5C%5Ca_n%20%3D%2010-4n%2B4%5C%5C%5C%5C%5Cunderline%7Ba_n%3D-4n%2B14%7D)
8)
-3, -10, -17, -24, ...
-10-(-3) = -7; -17-(-10) = -7; -24-(-17) = -7
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = -3
difference: d = -7
so the formula:
![a_n=a+d(n-1)\\\\a_n=-3+(-7)(n-1)\\\\a_n =-3-4n+7\\\\\underline{a_n=-7n+4}](https://tex.z-dn.net/?f=a_n%3Da%2Bd%28n-1%29%5C%5C%5C%5Ca_n%3D-3%2B%28-7%29%28n-1%29%5C%5C%5C%5Ca_n%20%3D-3-4n%2B7%5C%5C%5C%5C%5Cunderline%7Ba_n%3D-7n%2B4%7D)
9)
7, 8.5, 10, 11.5, ...
8.5-7 = 1.5; 10-8.5 = 1.5; 11.5-10 = 1.5
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 7
difference: d = 1.5
so the formula:
![a_n=a+d(n-1)\\\\a_n=7+1.5(n-1)\\\\a_n =7+1.5n-1.5\\\\\underline{a_n=1.5n+5.5}](https://tex.z-dn.net/?f=a_n%3Da%2Bd%28n-1%29%5C%5C%5C%5Ca_n%3D7%2B1.5%28n-1%29%5C%5C%5C%5Ca_n%20%3D7%2B1.5n-1.5%5C%5C%5C%5C%5Cunderline%7Ba_n%3D1.5n%2B5.5%7D)
10)
30, 22¹/₂, 15, 7¹/₂, ...
22¹/₂-30 = -7¹/₂; 15-22¹/₂ = -7¹/₂; 7¹/₂-15 = -7¹/₂
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 30
difference: d = -7¹/₂
so the formula:
![a_n=a+d(n-1)\\\\a_n=30+(-7\frac12)(n-1)\\\\a_n =30-7\frac12n+7\frac12\\\\ \underline{a_n=-7\frac12n+37\frac12}](https://tex.z-dn.net/?f=a_n%3Da%2Bd%28n-1%29%5C%5C%5C%5Ca_n%3D30%2B%28-7%5Cfrac12%29%28n-1%29%5C%5C%5C%5Ca_n%20%3D30-7%5Cfrac12n%2B7%5Cfrac12%5C%5C%5C%5C%20%5Cunderline%7Ba_n%3D-7%5Cfrac12n%2B37%5Cfrac12%7D)
First, plug in 448 for y:
448=7x+294
Secondly, subtract 294 from both sides to isolate x:
154=7x
Divide both sides by 7:
22=x
Refine:
x=22
The answer is D)22